P02.03 Microwave ablation enhances tumor-specific immune response in patients with hepatocellular carcinoma. (1st October 2020) - Staib, E; Leuchte, K; Thelen, M; Gödel, P; Lechner, A; Zentis, P; Garcia-Marquez, M; Waldschmidt, D; Datta, RR; Wahba, R; Wybranski, C; Zander, T; et al.
Abstract : Background: Thermal ablative therapies, such as microwave ablation (MWA) or radiofrequency ablation (RFA), are standard treatments for HCC. In addition to the local tumor destruction, abscopal effects (a reduction of a tumor mass in areas that were not included in the thermal ablation) could be observed. These systemic effects may be mediated by anti-tumor immune response, which has been described for RFA. MWA is rapidly replacing RFA, but systemic immunostimulatory effects of MWA treatment have been poorly studied. Materials and Methods: Patients receiving MWA for localized HCC were included in this study. Effects of MWA on peripheral blood mononuclear cells (PBMC) of HCC patients treated with MWA were analyzed by multicolor flow cytometry. Tumor-specific immune responses against 7 shared tumor antigens were analyzed using peptide pools in 3-color Fluorospot assays (Interferon-y/Interleukin-5/Interleukin-10). The impact of type, density and localization of tumor-infiltrating lymphocytes was assessed by immunohistochemistry (IHC) of CD3, CD4, CD8, FoxP3, CD38 and CD20 and digital image analyses (Immunoscore) of tumor specimens in an additional cohort of patients who received combined surgical resection and thermal ablation. Results: While comprehensive flow cytometric analyses in sequential samples (day 0, 7 and 90) of a prospective patient cohort (n=23) demonstrated only moderate effects of MWA on circulating immune cell subsets, Fluorospot analyses revealed de novo or enhanced tumor-specific immune responses in 30% of these patients. This anti-tumor immune response was related to tumor control. Interferon-y and Interleukin-5 T cell responses against cancer testis antigens were more frequent in patients with a long-time remission (>12 months) after MWA (7/16) compared to patients suffering from an early relapse (0/13 patients). Presence of tumor-specific T cell response (Interferon-y and/or Interleukin-5) was associated to longer progression-free survival (15.0 vs. 10.0 months). Immunohistochemical analyses of resected tumor samples revealed that a high T cell infiltration in a second tumor lesion at the time of thermal ablation was associated with superior disease-free survival (37.4 vs. 13.1 months). Conclusions: Our data demonstrates remarkable immune-related effects of MWA in HCC patients. This study and provides additional evidence for a combination of thermal ablation and immunotherapy in this challenging disease. Funding: 'Koeln Fortune' and 'CAP-CMMC' local research grant (to P.G. and H.A.S.) supported our research. Disclosure Information: E. Staib: None. K. Leuchte: None. M. Thelen: None. P. Gödel: None. A. Lechner: None. P. Zentis: None. M. Garcia-Marquez: None. D. Waldschmidt: None. R.R. Datta: None. R. Wahba: None. C. Wybranski: None. T. Zander: None. A. Quaas: None. U. Drebber: None. D.L. Stippel: None. C. Bruns: None. K. Wennhold: None. M. von Bergwelt-Baildon: None. H.A. Schlösser: None.